KOMUNIKASI VOKAL PADA BEKANTAN (Nasalis larvatus) - Mochamad Arief Soendjoto; Hadi Sukadi Alikodra; Mohammad Bismark; Heru Setijanto (Department of Forest Resources Conservation and Ecotourism - IPB University, 2003)
Vocal communication on the probosics monkey (Nasalis larvatus) was poorly documented. The objectives of the research were to phoentically identify vocalizations of this monkey, measure their durations and interpret their functions. Six vocalizations, along with eleven behaviors were found. Duration of four vocalizations ranged 0,36-1,30 sec and of two vocalizations was supposed to be less than 0,25 second. Vocalizations function to reflect the state of angry, happy or disappointed showed the domination 0,36-1,30 are an individual to others and warned the group. Keywords: comunications, vocalizations, the probocis monkey